Efficiency in SME: Malaysian evidence - Md Rus, Rohani; Zainudin, Nasruddin; Abdullah, Nur Adiana Hiau; Ahmad, Abdul Halim (2014)
Most studies on SMEs in Malaysia have looked at the performance of SMEs, especially by using the qualitative method.However, this study is different from previous studies where it offers a new insight of SMEs by looking at the efficiency of SME.Using 40 companies as the sample, this study analyse whether SME companies have used their current assets efficiently in getting sales.Surprisingly, the results show that most companies are not efficient in managing their current assets to produce sales. Since current asset or working capital is very crucial in running a business, the results might offer an insight of why most SMEs failed in their business.